O livre convencimento motivado no contexto do processo penal brasileiro - Giuberti, Glenio Puziol (2022)
This dissertation had as its object the analysis of the principle of free motivated conviction of the judge in the Brazilian criminal procedure. This object is linked to the area of concentration of the PPGDIR, that is, “Justice, Process and Constitution”, as well as in the line of research “Justice Systems, Constitutionality and Guardianship of Individual and Collective Rights”. It started from the research problem of the possibility of subjective judicial decisions in criminal proceedings, to reach the hypothesis of demonstrating that the free motivated conviction allows judicial decisions detached from the Law and the theses presented by the parties in the judicial process. It used the Critical Hermeneutic theory of Law (CHD), having as sources bibliographic works, as well as research on the jurisprudence of Brazilian higher courts on motivated free conviction and related topics. CHD aims to provide constitutionally adequate responses to the resolution of specific cases. This is the choice of the best argument in the process of justifying the judicial decision. It is concluded that the free conviction of the judge in the criminal process allows subjective decisions detached from the Law laid down and from the theses presented by the parties, violating the accusatory system in the Democratic State of Law, which treats as a fundamental right of the citizen the Law a constitutionally adequate judicial decision. Therefore, the free conviction motivated by article 155 of the CPP is undemocratic.